Ethnomathematics in the Room of the Rumah Gadang - Fauziah Fauziah; Niniwati Niniwati; Yusri Wahyuni (IndoMath: Indonesia Mathematics Education, 2020)
This study aims to analyze the exploration of ethnomathematics for basic information in the development of ethnomathematics science. The method of research that is carried out in an interview through a questionnaire and the data processed by the analysis of the taxonomy. A taxonomic analysis is carried out to make a category of cultural symbols that exist in culture were investigated. The object of research is how the shape of the room from the Rumah Gadang. From the analysis of data obtained Kenagarian that exist in the District of Solok South Most large house sieve which has a pavilion of 88.89% and shaped square- length, which has a bridge usual at Rumah Gadang amounted to 77.78% and which has a bridge -rise amounted to 7.4 %. Rumah Gadang has a room/room because the room/room is a place of privacy for the community both those who are married or not, so 88, 89 % of the Rumah Gadang have a room/room. And the number of booths/rooms vary depending on the house sieve of 40, 74 %, amounted to prima 37.04%, and amounted to even 11.11%